Interspecific Differences in the Larval Performance of Pieris Butterflies (Lepidoptera: Pieridae) Are Associated with Differences in the Glucosinolate Profiles of Host Plants. Issue 3 (30th April 2019) - Okamura, Yu; Tsuzuki, Natsumi; Kuroda, Shiori; Sato, Ai; Sawada, Yuji; Hirai, Masami Yokota; Murakami, Masashi
Abstract: The tremendous diversity of plants and herbivores has arisen from a coevolutionary relationship characterized by plant defense and herbivore counter adaptation. Pierid butterfly species feed on Brassicales plants that produce glucosinolates as a chemical deterrent against herbivory. In turn, the larvae of pierids have nitrile specifier proteins (NSPs) that are expressed in their gut and disarm glucosinolates. Pierid butterflies are known to have diversified in response to glucosinolate diversification in Brassicales. Therefore, each pierid species is expected to have a spectrum of host plants characterized by specific glucosinolate profiles. In this study, we tested whether the larval performance of different Pieris species, a genus in Pieridae (Lepidoptera: Pieridae), was associated with plant defense traits of putative host plants. We conducted feeding assays using larvae of three Pieris species and 10 species of the Brassicaceae family possessing different leaf physical traits and glucosinolate profile measurements. The larvae of Pieris rapae responded differently in the feeding assays compared with the other two Pieris species. This difference was associated with differences in glucosinolate profiles but not with variations in physical traits of the host plants. This result suggests that individual Pieris species are adapted to a subset of glucosinolate profiles within the Brassicaceae. Our results support the idea that the host ranges of Pieris species depend on larval responses to glucosinolate diversification in the host species, supporting the hypothesis of coevolution between butterflies and host plants mediated by the chemical arms race.